Transcatheter Tricuspid Valve Therapy: From Anatomy to Intervention - Cammalleri, Valeria; Carpenito, Myriam; Bono, Maria Caterina; Mega, Simona; Ussia, Gian Paolo; Grigioni, Francesco (Frontiers in Cardiovascular Medicine, 2021)
Nowadays millions of persons worldwide suffer for severe symptomatic tricuspid regurgitation (TR). However, the benefit of surgical correction of isolated secondary TR is not well established and the procedure has a non-negligible risk of periprocedural mortality and morbidity. In the recent years, in fact, novel transcatheter tricuspid valve interventions (TTVI) were developed for treating TR, so that TTVI is current considered in symptomatic, inoperable, anatomically eligible patients. TTVI can be divided into these 5 domains: edge-to-edge leaflet repair, tricuspid annuloplasty, caval implants, spacer and total valve replacement. Each transcatheter intervention has yet specific imaging needs to assess the feasibility and predict the procedural success. This review summarizes the available multimodality imaging tools for screening TR patients, and identifies anatomical characteristics to choose the best option for the patient.